Study of CP violation in B0 → DK⋆(892)0 decays with D → Kπ(ππ), ππ(ππ), and KK final states - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Herrero Gascón, Paula; Langenbruch, Christoph; et al. (Journal of high energy physics, 2024)
A measurement of CP-violating observables associated with the interference of B0 → D0K⋆(892)0 and B0 → D0K⋆(892)0 decay amplitudes is performed in the D0 → K∓π±(π+π−), D0 → π+π−(π+π−), and D0 → K+K− final states using data collected by the LHCb experiment corresponding to an integrated luminosity of 9 fb−1. CP-violating observables related to the interference of B0 s → D0 ¯K⋆(892)0 and B0 s → ¯D0 ¯K⋆(892)0 are also measured, but no evidence for interference is found. The B0 observables are used to constrain the parameter space of the CKM angle γ and the hadronic parameters rDK⋆ B0 and δDK⋆ B0 with inputs from other measurements. In a combined analysis, these measurements allow for four solutions in the parameter space, only one of which is consistent with the world average.
Im Text ist "0" jeweils und "⋆" hochgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, C. Cocha Toapaxi, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola,Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 12.05.2025